2014
DOI: 10.1364/ol.39.000766
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman spectroscopy with 0π pulses

Abstract: We developed a new variant of stimulated Raman spectroscopy with shaped short pulses, applicable to multiscattering media. The technique is based on the spectral modulation of the laser pulse due to the Raman scattering and may have a broad range of applications from spectroscopy and pathogen detection to microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Adiabatic passage population transfer in the λ system for different space positions inside the cell achieved with initial STIRAP pulses given by Eqs. ( 27) and (28) very efficient population transfer from the ground state to the excited vibrational state. The time behavior of STIRAP laser pulses are shown in Fig.…”
Section: Coherent Population Trapping Of Rotational and Vibrational L...mentioning
confidence: 99%
See 3 more Smart Citations
“…Adiabatic passage population transfer in the λ system for different space positions inside the cell achieved with initial STIRAP pulses given by Eqs. ( 27) and (28) very efficient population transfer from the ground state to the excited vibrational state. The time behavior of STIRAP laser pulses are shown in Fig.…”
Section: Coherent Population Trapping Of Rotational and Vibrational L...mentioning
confidence: 99%
“…Evolution of the STIRAP pulses for different space positions inside the cell filled with a three-level molecules achieved with initial STIRAP pulses given by Eqs. ( 27) and (28) It has a simple physical meaning and can be rewritten in the form of…”
Section: Propagation Effects For Stirap Pulsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that the optical 0π-pulses [30] under the condition of electromagnetically induced transparency (EIT) [31,32] are very sensitive to resonant interaction, and have advantages to be used in Raman spectroscopy. Moreover, the femtosecond 0π-pulses were successfully used for detection of twophoton absorption in non-radiative media.…”
Section: Introductionmentioning
confidence: 99%